Eight Weeks of Plyometric Training Improves Ability to Change Direction and Dynamic Postural Control in Female Basketball Players - Cherni, Yosser; Jlid, Mohamed Chedly; Mehrez, Hammami; Shephard, Roy J.; Paillard, Thierry; Chelly, Mohamed Souhaiel; Hermassi, Souhail (Frontiers in Physiology, 2019)
The aim of this study was to examine the effect of 8 weeks of plyometric training the ability to change direction and postural control in female basketball players. 25 national level female basketball players aged 18 to 27 years participated in the study. Volunteers were randomly assigned to an experimental group (n = 13) who replaced a part of their standard regimen by plyometric training twice weekly for 8 weeks, and a control group (n = 12) who continued their usual in-season training program. Before and after the intervention, the ability to change direction, and postural control were assessed by force platform under both static and dynamic conditions (with the eyes open and then closed). Isokinetic testing was also performed to calculate the Hamstring/Quadriceps (H/Q) strength ratio. The intervention improved ability to change direction (p ≤ 0.001, d = 1.51) and shortened path length (p = 0.038, d = 0.937) during static balance. However, it did not yield significant inter-group differences in postural control in the antero-posterior plane. The stance in the medio-lateral plane seems the most responsive to the intervention, with reductions in surface area (p = 0.012, d = 0.285), velocity with the eyes closed (p = 0.031, d = 0.968) and path length with the eyes open (p = 0.029, d = 0.968). The intervention did not change the H/Q ratio at the two speeds tested (60°.s-1, 120°.s-1). In summary, the addition of 8 weeks plyometric training to the usual in-season basketball regimen of top-level female basketball players enhanced their ability to change direction and reduced the risk of falls and injuries by improving postural control, but did not increase the H/Q measure of knee stability.